The Effect of Organizational Stress on the Efficiency of Hotel Employees: A Case of Van - NAS, Zekeriya; torun, zerrin (Atlas Journal, 2023)
Stress is a phenomenon that appears mostly in the working environments that individuals are exposed to and has a negative impact on performance. This research aimed to examine the level of stress experienced by hotel employees and their effects on their work performance. The results obtained from the survey conducted with 142 employees in the hotels in Van are included. In this research based on the quantitative method, hotel employees in Van constitute the universe of the study, and 142 people were surveyed as a sample. The demographic characteristics of the participants and the stress they experienced were evaluated in parallel, and the causes of stress were questioned by considering marital status, age, gender, education and working time